INDUCED GENETIC VARIABILITY IN COWPEA [VIGNA UNGUICULATA (L.)WALP] VAR. PUSA KOMAL - Induced variability; A. K. MEHTA (The Bioscan, 2014)
In the present investigation, cowpea var. Pusa Komal was treated with physical mutagen gamma rays (100, 200, 300, 400, 500 Gy) and chemical mutagen EMS (0.25%, 0.30%, 0.35%, 0.40% and 0.45%) with an objective to assess the genetic variability in M2 and M3 generation. Analysis of variance in M2 and M3 population showed significant differences among the treatments for all the twelve yield and its attributing characters under study except protein per cent. For all the characters under study in both the generations, phenotypic coefficient of variation was higher in magnitude than genotypic coefficient of variation. High GCV as well as PCV was obtained in M2 and M3 generation for traits number of primary branches per plant, protein percent, yield per plant and hundred seed weight. High heritability estimates in coupled with high genetic advance expressed as percent of mean was recorded in protein percent in M2 as well as M3 populations.